Extraction of two local types of cowpea (Vigna unguiculata L) proteins and study of its functional properties: Ethar Z. Naji - زكي ناجي ايثار (Journal of Kerbala for Agricultural Sciences, 2017)
A study of the chemical composition of the protein isolates of two types, white and red cowpea, (obtained from the local markets in Baghdad province), which have been extracted at pH 9.5 and sedimented at 4.5, showed a higher percentage of each of the moisture, ash, protein, and low carbohydrate for red cowpea protein isolate, reached 7.12%, 2.31%, 82.21% and 8.36% compared with 6.22% , 1.57% , 79.58% and 12.63% for white cowpea protein isolate respectively, the protein solubility at different pH values ranged between 2-9, showed a lowest solubility at pH 5 while the highest at pH 9, with the values of 4.82% , 2.99% at pH 5, 23.93% , 28.24% at pH 2, and 52.15%, 51.20% at pH 9, for white and red cowpea isolates respectively, the study showed also a higher water holding capacity and lowest oil holding capacity for red cowpea protein isolate, reaching 2.05 g water/ g protein compared with 1.39 gm water/ gm protein, and 1.68, 1.53 g fat/ g protein for white and red cowpea isolates respectively. A study of the functional properties of the protein isolates at pH values 3-9, showed that a lowest were at pH 5, they were for emulsifying index 12.00% , 15. 60%, emulsion stability 15.4% , 12.6%, foaming ability 18.19% , 14.99%, and foam stability 14.89% , 12.23% for white and red cowpea protein isolate respectively, while the maximum was at pH 9 reaching, emulsifying index 80.76%, 75.41%, emulsion stability 80.9% , 90.65, foaming ability 85.43%, 83.33%, and foam stability 70.54%, 66.90% for white and red protein isolate respectively, using different concentrations ranged from 2-20 %, showed that the lowest concentration needed to form a gel was 14% of the white cowpea protein isolate, and 12% for the red one, and not configure a static gel, unless the concentration was 16% for the tow samples of the study.